Water and Oil Repellent Surfaces - Karapanagiotis, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Materials of extreme wetting properties have received significant attention, as they offer new perspectives providing numerous potential applications. Water- and oil-repellent surfaces can be used, for instance, in the automobile, microelectronics, textile and biomedical industries; in the protection and preservation of constructions, buildings and cultural heritage; and in several other applications relevant to self-cleaning, biocide treatments, oil-water separation and anti-corrosion, just to name a few. The papers included in this book present innovative production methods of advanced materials with extreme wetting properties that are designed to serve some of the abovementioned applications. Moreover, the papers explore the scientific principles behind these advanced materials and discuss their applications to different areas of coating technology.